1980
DOI: 10.1901/jaba.1980.13-355
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Influences on Alcoholics' Rates of Alcohol Consumption

Abstract: Two experiments were designed to examine modeling influences on alcoholics' alcohol consumption. Three male alcoholics were paired with confederates, posing as alcoholics. In Experiment 1, alcoholic-confederate pairs participated in a 1-hour taste-rating task, which involved rating different wines on a list of adjectives. Experiment 2 consisted of 1-hour ad lib access to wine in a naturalistic bar setting. In both experiments, confederates alternated 15-minute periods of heavy and light consumption, drinking f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…Some suggest that drinking behavior may be influenced through social modeling (Caudill & Lipscomb, 1980;Caudill & Marlatt, 1975;Collins & Marlatt, 1981;Collins, Parks, & Marlatt, 1985;Quigley & Collins, 1999;Wood, Read, Palfai, & Stevenson, 2001). This is consistent with findings that indicate adolescents with higher exposure to adults and peers who drink are more likely to drink, to begin drinking at an earlier age, to drink more frequently, and to consume larger quantities of alcohol.…”
Section: Part Three: Findings and Discussionsupporting
confidence: 78%
“…Some suggest that drinking behavior may be influenced through social modeling (Caudill & Lipscomb, 1980;Caudill & Marlatt, 1975;Collins & Marlatt, 1981;Collins, Parks, & Marlatt, 1985;Quigley & Collins, 1999;Wood, Read, Palfai, & Stevenson, 2001). This is consistent with findings that indicate adolescents with higher exposure to adults and peers who drink are more likely to drink, to begin drinking at an earlier age, to drink more frequently, and to consume larger quantities of alcohol.…”
Section: Part Three: Findings and Discussionsupporting
confidence: 78%
“…Initial research on the effect of modeled consumption rates on social drinking (Caudill & Marlatt, 1975) suggested that heavy-drinking men tended to match the consumption of their drinking partner whether his consumption was heavy or light. Subsequent examinations of this phenomenon replicated these findings in laboratory analogue drinking tasks such as the taste-rating task (Cooper, Waterhouse, & Sobell, 1979;Hendricks, Sobell, & Cooper, 1978;Lied & Marlatt, 1979;Watson & Sobell, 1982), natural bar settings (Reid, 1978), and seminaturalistic bar settings (Caudill & Lipscomb, 1980).…”
mentioning
confidence: 75%
“…Third, only studies were included in which effect sizes could be calculated from the statistics reported in the article (i.e., means, standard deviations and sample size, or inferential statistics for the comparison between heavy and light model conditions). (1) Of the 14 articles identified, four (Caudill and Lipscomb, 1980;DeRicco and Garlington, 1977;DeRicco and Niemann, 1980;Garlington and DeRicco, 1977) did not provide adequate statistics for the calculation of effect sizes and were dropped from the subsequent analysis. We were able to obtain two of the three unpublished dissertations (Becotte, 1987, andWilkins, 1980).…”
Section: Inclusion Of Studiesmentioning
confidence: 99%